EFFICIENCY ASSESSMENT OF SOME DANUBE PORTS BY USING DEA WINDOW ANALYSIS - Gheorghe MATEI (Scientific Journal of Silesian University of Technology. Series Transport)
The aim of this paper is to empirically assess the efficiency / inefficiency of five Danube ports in five neighbouring countries and to observe how it evolves over an eight-year period ranging from 2014 to 2021. The five ports are located on the lower course of the Danube River and are the most important in their states: Smederevo (Serbia), Ruse (Bulgaria), Galați (Romania), Giurgiulești (Moldova), and Izmail (Ukraine). The study uses a mixed-method, namely the Data Envelopment Analysis (DEA) window analysis method and Andersen and Petersenʼs super-efficiency model to evaluate the efficiency of these ports over time. Port efficiency analysis is based on a single output, i.e. the cargo throughput, and four inputs: the total port area, the total area of warehouses, the quay length, and the number of cranes. It was determined that none of the five ports analysed reaches the maximum efficiency of 1.000, their average efficiency being quite low, only 0.631. The highest average efficiency is recorded by the Serbian port of Smederevo, with 0.768, this port being found to make good use of its resources for production. On the other extreme, the Bulgarian port of Ruse was found to be the least efficient port, obtaining the lowest average efficiency over an eight-year period, with only 0.360. The study tries to capture the causes of the inefficiency of selected ports and propose some measures to improve their efficiency.